A Comparative Assessment of Autologous Conditioned Serum and Ozone for Knee Osteoarthritis Treatment: Mid-Term Follow up - Hashemi, Masoud; Adlkhoo, Hossein; Dadkhah, Payman; Rohanifar, Ramin; Taheri, Mehrdad (Novelty in Biomedicine, 2020)
Background: Knee osteoarthritis is a common disease associated with knee pain, physical disability, and joint stiffness. The use of non-surgical treatment methods in patients with knee osteoarthritis is important. Autologous conditioned serum (ACS) is a new regenerative therapeutic method that was investigated by a limited number of clinical trials. So far, using ACS in patients with Knee osteoarthritis remains to be controversial among physicians. Thus, the current study was carried out to compare the therapeutic effects of intra-articular ACS and ozone injections in patients with knee osteoarthritis. Materials and Methods: This prospective, double-blind randomized clinical trial was conducted among 60 patients (30= interleukin-1 receptor antagonist (IL-1Ra) group, 30= ozone group) with knee osteoarthritis, who referred to the Pain Management Clinic of Akhtar Educational Hospital during 2018 to 2019. In the IL-1Ra group, 2 ml of IL-1Ra was injected into the knee joint. The regimen protocol consisted of 4 injections, performed on the first, seventh, fourteenth, and twenty-first days of the treatment and ozone group, 10 ml of ozone (30 μg/ml) + 5 ml of lidocaine 1% were injected into the knee joint. The regimen protocol consisted of 3 injections, performed on the first day of the treatment, one month after the first injection, and two months after the first injection. The severity of pain was assessed by the patients’ self-report of pain and using the visual analog scale (VAS), before the treatment and 1, 3 and 6 months after the treatment. The Knee Injury and Osteoarthritis Outcome Score (KOOS) and the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) questionnaires were also measured at before and 6 months following treatment. Results: The changes in the VAS pain at different time periods showed statistically significant differences in the two groups, (P=0.0001). There was no significant difference between the two groups before the treatment and one month and three months after the initiation of the treatment; however, there was a significant difference between the two groups six months after the initiation of the treatment (P=0.0001). KOOS scores of symptoms, daily activities, and athletic and recreational functions were significantly higher in the IL-1Ra group, and the WOMAC scores of physical function and joint stiffness and the overall scores were significantly higher in the IL-1Ra group, (p<0.05). Conclusion: The intra-articular injection of IL-1Ra is a low-invasive, safe, effective, and long-acting method. In patients with knee osteoarthritis, clinical improvements and responses to the intra-articular IL-1Ra injection are better and longer compared to ozone injection. Therefore, it can be considered as a suitable choice in treating patients with chronic knee pain.